2020
DOI: 10.1097/md.0000000000020039
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic safety of laparoscopic radical cholecystectomy in pT2 gallbladder cancer

Abstract: The role of laparoscopic radical cholecystectomy (LRC) in the surgical management of T2 gallbladder carcinoma (GBC) is still controversial. The medical records of patients with T2 GBC treated with radical cholecystectomy were retrospectively reviewed. In this study, we compare the short- and long-term oncologic outcomes, using propensity score matching analysis, of patients with T2 GBC who underwent LRC and open radical cholecystectomy (ORC). Among 183 patients, 86 were selected by prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 37 publications
0
21
0
2
Order By: Relevance
“…If there is a possibility of bladder invasion of the urethra, the total urethra should be removed intraoperatively in combination. In younger male patients who require preservation of sexual function, intraoperative care should also be taken to protect the associated nerve and vascular tissues [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…If there is a possibility of bladder invasion of the urethra, the total urethra should be removed intraoperatively in combination. In younger male patients who require preservation of sexual function, intraoperative care should also be taken to protect the associated nerve and vascular tissues [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The gallbladder was considered to be free of liver invasion, and cholecystectomy was performed by peeling off the gallbladder plate instead of combine liver wedge resection. The effect of combined liver resection in radical cholecystectomy is still controversial, but recent studies [ 18 - 20 ] have shown no difference in survival, and further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this same group also compared these outcomes to laparoscopic radical cholecystectomy and reported a significant decrease in operative time, estimated blood loss, and length of stay. However, these benefits were at the cost of a significant decrease in lymph node retrieval [ 33 ].…”
Section: Discussionmentioning
confidence: 99%